Message from the Chief Editor - Editor, Chief (Journal of Technical Education and Training, 2016)
Welcome to issue 2, volume 8 of the Journal of Technical Education and Training (JTET). I am happy to present seven papers in this issue that share some aspects of TVET practices in Indonesia, Malaysia, Nigeria, Philippine, South Africa and Tanzania. Concerns highlighted in this issue are mostly with employment and employability issues and management of TVET. Successful employment has been an explicit goal of TVET be it to be employed by others or self-employed.  To be employed and to be self-employed require different sets of skills which needs to be ascertained and developed. Employment by others requires graduates to have the skills profile demanded by the target employers. Gaps in desired skills would result in unemployment. In the first paper, Ayonmike & Okeke highlight the skills gaps that are prevalent among vocational graduates in Nigeria and suggest potential means of reducing the gap through institutions and industry partnerships that seek to improve curriculum design and utilisation of resources. Entrepreneurial courses have been added to TVET curriculum to enhance graduate employment especially with regard to self-employment. The success of these courses however depends to a certain extent on the entrepreneurial intention of enrolled students. Thus, in the second paper Ana et al.  report on the entrepreneurial intention among TVET secondary schools students in Malaysia and Indonesia. Information obtained on the entrepreneurial intentions of TVET students in the two nations provides some indication of the situation in South East Asia.Getting employed is good but learning does not stop once TVET graduates gain employment. At the work place graduates have to continue seeking knowledge and skills to prosper in their career and to become leaders in their respective field. To be a good leader requires an individual to have leadership skills which are – more often than not - acquired on the job through lifelong learning. As such, leadership skills are sometimes poorly developed leading to less than optimum performance of the affected industry. In the third paper Wan Muda et al., report on the leadership skills of Malaysian construction industry leaders, providing an example from the perspective of a developing nation.  Information gained from their study help TVET providers to be more cognizant of the necessary leadership skills in the construction industry of a developing nation.  Going back to Africa, TVET as a second choice is still prevalent resulting in less than ideal enrolment in some programmes. In the fourth paper, Mulongo, Kitururu, & Irira look at efforts that can be made to improve the marketability of TVET in Tanzania which is expected to lead to better TVET acceptance and enrolments. In addition to public providers, private TVET providers are gaining greater importance in Africa as they continue to give more offerings of TVET programmes to this nation. In the fifth paper, Akoojee addresses the lack of understanding regarding TVET that are offered by private providers as well as their roles and contributions to the TVET sector in Africa.Planning and managing TVET institutions, programmes and resources is a constant challenge to TVET managers. In the sixth paper, Suharno provides an example of the integration of two management tools, SWOT analysis method and balance score card in conducting strategic planning for TVET in Indonesia.  In addition to these tools, technology is also playing an important role in the management and in the teaching and learning of TVET. From the Philippines, Tapado reports on the prospects and problems in the usage of ICT as tools for teaching and learning and management in one of the most established TVET higher institutions in the Philippines.  I hope our readers find the articles useful for which I would like to thank our contributing authors, reviewers and editors. Last but not least, Happy New Year and may the coming year brings good tidings to everyone.  Professor Dr. Maizam AliasChief Editor